Features of body reactions in children with oncological diseases during intravenous anesthesia with propofol - V.I. Snisar; D.V. Myronov (Zdorovʹe Rebenka, 2022)
Background. Surgery is one of the cornerstones of cancer treatment. Recently, total intravenous anesthesia (TIA) has become more popular and practical in oncological surgeries due to several main reasons. However, it is important to assess the adaptive reactions of children who undergo surgical treatment and anesthesia. The objective: to study the compensatory and adaptive mechanisms in response to surgical and anesthetic stress, adequacy of TIA in children with oncological diseases by assessing the level of stress hormones and indicators of heart rate variability. Materials and methods. Twenty-three children with cancer aged 10.68 ± 4.51 years (first group) were examined, and also 27 children aged 9.30 ± 3.85 years (second group) were operated for minor trauma. Surgeries in children of both examined groups were performed under total intravenous anesthesia with propofol. Results. Already at the second stage of observation, 100 % of patients in the first group had a significant decrease in systolic blood pressure. As for trauma patients, only 92.59 % of them had a decrease in the level of systolic pressure on the background of TIA at the second stage, and 77.77 % of patients had it even at the third stage. Analyzing the parameters of heart rate variability, we saw that 30.43 % of cancer patients already at the second stage of the research had an increase in the level in the high frequency range. As for the power of the low-frequency spectrum, its decrease was noted in half of the patients. All examined people had elevated cortisol levels. However, children with tumors had a 2.8-fold its increase, trauma patients — a 4.4-fold increase. At the same time, children with cancer had higher initial level of cortisol. Conclusions. Children with oncology and children with trauma have different profiles of stress reactions. Total intravenous anesthesia with propofol improved the outcomes of surgical treatment by suppressing extreme stress reactions. Further research is needed to understand how to optimize the modulation of stress responses and to find precise markers for optimal modulation.